2018
DOI: 10.15406/sij.2018.02.00037
|View full text |Cite
|
Sign up to set email alerts
|

The psychology of giving behavior in islam

Abstract: Waqf is a financial charitable endowment established by withholding immovable and movable properties to perpetually spend its revenue on fulfilling public needs, once the property is created as Waqf, it could never be given as gift, inherited, or sold. Traditionally, Waqf was inculcated in Muslims' culture, and has included in all walks of life. When it was the main source for various public services that been provided to communities. Therefore, Muslims in all over the world are exposed to participate in Waqf,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
11
0
1
Order By: Relevance
“…Further support was documented in the prior literature. Several studies confirmed that cash waqf collection can be leveraged through convenience (Baqutayan et al, 2018;Anwar et al, 2019;. More support was seen in the study of Jih (2007), who verified that convenience and an individual's decisionmaking are highly correlated.…”
Section: Discussionmentioning
confidence: 86%
“…Further support was documented in the prior literature. Several studies confirmed that cash waqf collection can be leveraged through convenience (Baqutayan et al, 2018;Anwar et al, 2019;. More support was seen in the study of Jih (2007), who verified that convenience and an individual's decisionmaking are highly correlated.…”
Section: Discussionmentioning
confidence: 86%
“…48 It also increases positive emotions such as happiness, satisfaction, and different feelings. Baqutayan (2018) 49 stated that there are many benefits associated with giving charity, such as God blessing (including avoiding harm/danger), psychological comfort, Happiness and joy, Self-satisfaction (charity can lead to other people's satisfaction, self-satisfaction, and pleasing Allah swt), and multiple rewards (QS Al Hadid 18). Moreover, the charity was given during the current Covid-19 pandemic, where many people lacked property and food.…”
Section: Islamic Counseling In Forming Religious Copingmentioning
confidence: 99%
“…It refers to an individual performing the behavior or act because he or she feels happy doing it, or because of curiosity or interest. An intrinsically motivated person is more likely to have better mental health and general wellbeing than an extrinsically motivated person (Baqutayan et al, 2018). Furthermore, sense of obligation is one of the factors contributed to good deeds in western perspective.…”
Section: Good Deeds From Islamic and Western Perspectivesmentioning
confidence: 99%